Efforts to Increase Knowledge of Clean and Healthy Living - Rafika Aini; Dewi Fitriani; Makmur Hidayat; Rahmadhani; Maisharoh (CV. Get Press Indonesia, 2024)
Clean and Healthy Living Behavior (PHBS) is an action taken to improve individual and community health through daily habits that support cleanliness and health. This empowerment aims to understanding of PHBS through educational programs involving lectures, discussions and questions and answers. This program was held on 23-24 September 2023 and was attended by 57 grade 7 students. The pre-test and post-test results showed an increase in students' knowledge from an average score of 6.49 to 8.91, indicating the effectiveness of the educational program in increasing awareness and knowledge about PHBS. The main emphasis in this program is the importance of washing hands properly to prevent disease, as well as the role of a clean school environment in supporting student health and learning achievement. The research conclusion shows that education about PHBS is effective in increasing students' knowledge, which in turn can contribute to creating a healthier school environment and supporting learning achievement. Support from families and schools, as well as the active role of the School Health Unit (UKS), is very important in maintaining and improving clean and healthy living behavior among students.